Swedish - Finnish glossary: congestion tax - Language Council of Sweden, Institute for Language and Folklore (Institute for Language and Folklore, 2020)
Swedish - Finnish glossary with congestion tax words. Contains approximately 120 entries. 2006.

Swedish - Finnish glossary with congestion tax words. Contains approximately 120 words. 2006.

Svensk-sverigefinsk ordlista med trängselskattord. Innehåller ca 120 uppslagsord. 2006.
Svensk-finsk ordlista: trängselskatt
Keywords: traffic regulations; trafikbestämmelse; road tax; vägskatt; Taxes; Skatter; commuter traffic; pendlartrafik; glossary; ordlista; environmental tax; miljöskatt; taxation; beskattning; traffic control measure; trafikövervakningsåtgärd; urban traffic; stadstrafik; word list; ordlista; Language and linguistics; Språk och lingvistik; Languages and Literature; Språk och litteratur